Mesoscopic Optical Imaging of the Pancreas—Revisiting Pancreatic Anatomy and Pathophysiology - Alanentalo, Tomas; Hahn, Max; Willekens, Stefanie M. A.; Ahlgren, Ulf (Frontiers in Endocrinology, 2021)
The exocrine-endocrine multipart organization of the pancreas makes it an exceedingly challenging organ to analyze, quantitatively and spatially. Both in rodents and humans, estimates of the pancreatic cellular composition, including beta-cell mass, has been largely relying on the extrapolation of 2D stereological data originating from limited sample volumes. Alternatively, they have been obtained by low resolution non-invasive imaging techniques providing little detail regarding the anatomical organization of the pancreas and its cellular and/or molecular make up. In this mini review, the state of the art and the future potential of currently existing and emerging high-resolution optical imaging techniques working in the mm-cm range with μm resolution, here referred to as mesoscopic imaging approaches, will be discussed regarding their contribution towards a better understanding of pancreatic anatomy both in normal conditions and in the diabetic setting. In particular, optical projection tomography (OPT) and light sheet fluorescence microscopy (LSFM) imaging of the pancreas and their associated tissue processing and computational analysis protocols will be discussed in the light of their current capabilities and future potential to obtain more detailed 3D-spatial, quantitative and molecular information of the pancreas.